Bolhas de ódio: o ódio como componente político nas dinâmicas interacionais societárias mediadas por Tecnologias de Comunicação Instantânea (TCIs) - Lobo, Denis Augusto Carneiro (2018)
This master’s thesis analyses the constitution of the so-called Hate Speech in Digital Social Networks (DSNs), specifically, on Facebook. Starting from users’ text interactions in public Facebook pages of the 2014 presidential candidates Dilma Rousseff (Workers Party) and Aécio Neves (Brazilian Social Democracy Party) during the presidential run (August to October 2014), I’ve searched for the characterization of this phenomena within a political-party polarization scenario. Focusing in the political constitution of the referred phenomena, I’ve then evidenced the difference between the legal concept of Hate Speech and a more widespread phenomena, which worked in this scenario as a political component of the social interactions: the political hate. Furthermore, the debate gets centralized in the mediation process of social interactions in an Instant Communication Technology (ICTs) scenario, in search of a confluence with the Latin American studies about the process of technological and communicational mediation, its diferences and implications in an Interactional Sociology. Finally, having analysed such studies as a theorical and methodological background, I've presented a discussion about the importance of the new computational techniques such as "filter bubbles", "social bots" and User Experience (UX) in the daily life of today's liberal democracies, leading the debate to the establishment of "fear techniques", clearly an expression of the so-called "Fear Culture", to which many authors refeer today